تحليل النظم التصنيعية ودراسة نظام تقليل الفاقد - سمير نمر كفا (Tishreen University, 2019)
يتناول البحث دراسة مشكلة بناء خطوط الإنتاج، وإيجاد الفاقد الأمثل وعلاقته بتقليل الكلفة العامة. ونهتم في هذا البحث بأنموذج محدد من خطوط الإنتاج وهي خطوط الإنتاج المستمر المستخدم في الصناعات الثقيلة. ويتم ذلك من خلال الدراسة المرجعية لتوازن خطوط الإنتاج واقتراح أنموذج رياضي يعتمد على علم بحوث العمليات والبرمجة الخطية وذلك بتمثيل هدف البحث ومحدداته بجملة معادلات رياضية تحل بمساعدة برنامج الـMATLAB وحزمة Optimization. ودراسة علاقة ذلك بسياسة تقليل الفاقد ونظام إدارة الجودة الشاملة في المؤسسات الصناعية.   This study deals with the building problems of production lines, finding out the optimum loss relationship with general cost reduction. It also deals with a definite model of continuous production lines used in heavy industries. This research is carried out by reference studies for balancing production lines and proposing a mathematical program that depends on the science of operational research and linear programming. This helps model the research aims and its determinants on a mathematical group of equations that could be solved by the MatLab program. This could also be studied in terms of its optimization and its relation to political-educational costs and the general feasibility policy of industrial establishments.